2003
DOI: 10.1207/s15327914nc4602_03
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Index, Glycemic Load, and Incidence of Endometrial Cancer: The Iowa Women's Health Study

Abstract: Although specific foods or nutrients have not been linked consistently with risk of endometrial cancer, obesity and diabetes are associated with increased risk. These conditions may be influenced by the glycemic index or load of the usual diet. We therefore examined the association of glycemic index and load measured at baseline using a food frequency questionnaire in a cohort of 23335 postmenopausal women. Over 15 yr of follow-up, we identified 415 incident endometrial cancers. The average glycemic index was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 22 publications
5
72
1
3
Order By: Relevance
“…Unlike Folsom et al 15 we did not collect data on diabetes, and therefore were unable to adjust for it in the analysis. However, although there is evidence from epidemiological studies to support a causal association between diabetes mellitus and endometrial cancer 32 , it is not immediately obvious that failure to adjust for diabetes would have confounded the associations observed here.…”
Section: Discussionmentioning
confidence: 97%
“…Unlike Folsom et al 15 we did not collect data on diabetes, and therefore were unable to adjust for it in the analysis. However, although there is evidence from epidemiological studies to support a causal association between diabetes mellitus and endometrial cancer 32 , it is not immediately obvious that failure to adjust for diabetes would have confounded the associations observed here.…”
Section: Discussionmentioning
confidence: 97%
“…Body mass index and diabetes status were determined as previously described (7). A woman's physical activity level was categorized from three questions regarding frequency of moderate and vigorous activities and dichotomized as low or moderate/ high.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 16 published articles reporting risk factor of endometrial cancer satisfied the inclusion criteria and were included in our meta-analysis (Levi et al, 1993;Potischman et al, 1993;Shu et al, 1993;Tzonou et al, 1996;Goodman et al, 1997;Jain et al, 2000;McCann et al, 2000;Littman et al, 2001;Petridou et al, 2002;Folsom et al, 2003;Furberg et al, 2003;Xu et al, 2007;Bravi et al, 2009;Yeh et al, 2009;Biel et al, 2011b;Cui et al, 2011). The characteristics of the included studies were shown in Table 1.…”
Section: Eligible Studiesmentioning
confidence: 99%